# 11X1 T14 09 mathematical induction 2 (2010)

Post on 05-Dec-2014

560 views

Embed Size (px)

DESCRIPTION

TRANSCRIPT

- 1. Mathematical Induction
- 2. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3
- 3. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1
- 4. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6
- 5. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6 which is divisible by 3
- 6. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6 which is divisible by 3 Hence the result is true for n = 1
- 7. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6 which is divisible by 3 Hence the result is true for n = 1 Step 2: Assume the result is true for n = k, where k is a positive integer
- 8. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6 which is divisible by 3 Hence the result is true for n = 1 Step 2: Assume the result is true for n = k, where k is a positive integer i.e. k k 1k 2 3P, where P is an integer
- 9. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6 which is divisible by 3 Hence the result is true for n = 1 Step 2: Assume the result is true for n = k, where k is a positive integer i.e. k k 1k 2 3P, where P is an integer Step 3: Prove the result is true for n = k + 1
- 10. Mathematical Induction e.g. iii Prove n n 1 n 2 is divisible by 3 Step 1: Prove the result is true for n = 1 123 6 which is divisible by 3 Hence the result is true for n = 1 Step 2: Assume the result is true for n = k, where k is a positive integer i.e. k k 1k 2 3P, where P is an integer Step 3: Prove the result is true for n = k + 1 i.e. Prove : k 1k 2k 3 3Q, where Q is an integer
- 11. Proof:
- 12. Proof: k 1k 2k 3
- 13. Proof: k 1k 2k 3 k k 1k 2 3k 1k 2
- 14. Proof: k 1k 2k 3 k k 1k 2 3k 1k 2 3P 3k 1k 2
- 15. Proof: k 1k 2k 3 k k 1k 2 3k 1k 2 3P 3k 1k 2 3P k 1k 2
- 16. Proof: k 1k 2k 3 k k 1k 2 3k 1k 2 3P 3k 1k 2 3P k 1k 2 3Q, where Q P k 1k 2 which is an integer
- 17. Proof: k 1k 2k 3 k k 1k 2 3k 1k 2 3P 3k 1k 2 3P k 1k 2 3Q, where Q P k 1k 2 which is an integer Hence the result is true for n = k + 1 if it is also true for n = k
- 18. Proof: k 1k 2k 3 k k 1k 2 3k 1k 2 3P 3k 1k 2 3P k 1k 2 3Q, where Q P k 1k 2 which is an integer Hence the result is true for n = k + 1 if it is also true for n = k Step 4: Since the result is true for n = 1, then the result is true for all positive integral values of n by induction.
- 19. iv Prove 33n 2n2 is divisible by 5
- 20. iv Prove 33n 2n2 is divisible by 5 Step 1: Prove the result is true for n = 1
- 21. iv Prove 33n 2n2 is divisible by 5 Step 1: Prove the result is true for n = 1 33 23 27 8 35
- 22. iv Prove 33n 2n2 is divisible by 5 Step 1: Prove the result is true for n = 1 33 23 27 8 35 which is divisible by 5
- 23. iv Prove 33n 2n2 is divisible by 5 Step 1: Prove the result is true for n = 1 33 23 27 8 35 which is divisible by 5 Hence the result is true for n = 1
- 24. iv Prove 33n 2n2 is divisible by 5 Step 1: Prove the result is true for n = 1 33 23 27 8 35 which is divisible by 5 Hence the result is true for n = 1 Step 2: Assume the result is true for n = k, where k is a positive integer i.e. 33k 2k 2 5P, where P is an integer
- 25. iv Prove 33n 2n2 is divisible by 5 Step 1: Prove the result is true for n = 1 33 23 27 8 35 which is divisible by 5 Hence the result is true for n = 1 Step 2: Assume the result is true for n = k, where k is a positive integer i.e. 33k 2k 2 5P, where P is an integer Step 3: Prove the result is true for n = k + 1 i.e. Prove : 33k 3 2k 3 5Q, where Q is an integer
- 26. Proof:
- 27. Proof: 33k 3 2k 3
- 28. Proof: 33k 3 2k 3 27 33k 2k 3
- 29. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3
- 30. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3
- 31. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 135P 27 2k 2 2 2k 2
- 32. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 135P 27 2k 2 2 2k 2 135P 25 2k 2
- 33. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 135P 27 2k 2 2 2k 2 135P 25 2k 2 527 P 5 2k 2
- 34. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 135P 27 2k 2 2 2k 2 135P 25 2k 2 527 P 5 2k 2 5Q, where Q 27 P 5 2k 2 which is an integer
- 35. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 135P 27 2k 2 2 2k 2 135P 25 2k 2 527 P 5 2k 2 5Q, where Q 27 P 5 2k 2 which is an integer Hence the result is true for n = k + 1 if it is also true for n = k
- 36. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 135P 27 2k 2 2 2k 2 135P 25 2k 2 527 P 5 2k 2 5Q, where Q 27 P 5 2k 2 which is an integer Hence the result is true for n = k + 1 if it is also true for n = k Step 4: Since the result is true for n = 1, then the result is true for all positive integral values of n by induction.
- 37. Proof: 33k 3 2k 3 27 33k 2k 3 275P 2k 2 2k 3 135P 27 2k 2 2k 3 Exercise 6N; 3bdf, 4 ab(i), 9 135P 27 2k 2 2 2k 2 135P 25 2k 2 527 P 5 2k 2 5Q, where Q 27 P 5 2k 2 which is an integer Hence the result is true for n = k + 1 if it is also true for n = k Step 4: Since the result is true for n = 1, then the result is true for all positive integral values of n by induction.